2021
DOI: 10.3390/antiox10091386
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Prevents Binge Alcohol-Induced Leaky Gut and Liver Injury through Inhibiting Gut Dysbiosis and Oxidative Stress

Abstract: Alcoholic liver disease (ALD) is a major liver disease worldwide and can range from simple steatosis or inflammation to fibrosis/cirrhosis, possibly through leaky gut and systemic endotoxemia. Many patients with alcoholic steatohepatitis (ASH) die within 60 days after clinical diagnosis due to the lack of an approved drug, and thus, synthetic and/or dietary agents to prevent ASH and premature deaths are urgently needed. We recently reported that a pharmacologically high dose of pomegranate extract prevented bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…The intestinal microflora plays an important role in maintaining intestinal microenvironment homeostasis ( Liu et al, 2019 ). Previous studies have revealed an increase in the abundance of Firmicutes and Lactobacillus species and a decrease in the abundance of Verrucomicrobia and Bacteroidetes species in mice after polyphenols supplementation ( Kim et al, 2021 ; Lu et al, 2021 ). Our results demonstrated that EA supplementation decreased the count of E. coli but increased the count of Lactobacillus species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The intestinal microflora plays an important role in maintaining intestinal microenvironment homeostasis ( Liu et al, 2019 ). Previous studies have revealed an increase in the abundance of Firmicutes and Lactobacillus species and a decrease in the abundance of Verrucomicrobia and Bacteroidetes species in mice after polyphenols supplementation ( Kim et al, 2021 ; Lu et al, 2021 ). Our results demonstrated that EA supplementation decreased the count of E. coli but increased the count of Lactobacillus species.…”
Section: Discussionmentioning
confidence: 98%
“…The intestinal antioxidant capacity is also crucial for maintaining intestinal health ( Kim et al, 2021 ). The body has a series of defense mechanisms for controlling oxidative stress; one of these is the enzymatic antioxidant system ( Pari and Sivasankari, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mice in the treatment group were subjected to oral administration of a daily dose of 60 mg/kg EA (Solarbio, Beijing, China) (add 0.6 g of EA to 100 mL normal saline. )for 14 days before performing surgery to model liver ischemia [ 20 ]. The experiment design is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The research from Elyamany M. shows that EA treatment can significantly reduce the liver damage caused by valproic acid in rats [ 18 ], and L. Gu et al demonstrated that EA protected against LPS/GalN-induced liver injury in SD rats by enhancing the antioxidative defense system and reducing the inflammatory response [ 19 ]. Kim, D described a significant reduction in endotoxemia and inflammatory liver damage with EA treatment by inhibiting the imbalance of the intestinal flora in c57 mice, elevated oxidative stress and apoptosis marker proteins [ 20 ]. However, the effect and underlying specific molecular mechanisms of EA on hepatic IRI remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms are causing a leaky intestine; they are still incompletely understood and subject to vibrant research. Such mechanisms include physical trauma and toxins such as alcohol, TJ severance, altered epithelial stem cell turnover, and alterations to the mucus layer texture [ 48 , 49 ]. Emerging research points towards a close relationship between gut microbiome alterations, intestinal leakiness, and autoimmunity [ 50 ].…”
Section: Intestinal Barrier Function In Liver Diseasesmentioning
confidence: 99%